Criticize the Legality of the People's Republic of China Claims the Nine Dash Line under International Law - Irsyad, Muhammad Ghaffaar; Khanif, Al (The Indonesian Journal of International Clinical Legal Education, 2023)
This study aims to find out and analyze the legality of the PRC's claim to the Nine Dash Line based on the historical claim of the PRC's Traditional Fishing Right in the South China Sea (SCS) from the perspective of international law sourced from the United Nations Convention on the Law of the Sea 1982 and PRC efforts to defend their claims in the SCS from countries with both claims and interests. This type of research is normative legal research using the Statute Approach and the Conceptual Approach. This study concludes that if you look at UNCLOS 1982, the PRC's claim to the Nine Dash Line cannot be maintained as a territorial claim because UNCLOS 1982 does not regulate how to determine the baseline based on historical claims, and according to UNCLOS 1982 handles the drawing of the baseline in 3 ways. Then, the PRC, in defending its claims, used various means such as the military occupation of uninhabited islands, increased military force, and deployment of ADIZs. In addition, the PRC also divided ASEAN in taking a stand on the SCS dispute.